Dysbiosis of the human skin mycobiome in patients receiving systemic IL-23 inhibitors - Yuta Koike; Sayaka Kuwatsuka; Daisuke Motooka; Hiroyuki Murota (Allergology International)
Background: Systemic inhibition of pro-inflammatory cytokines affects the skin microbiome; however, the impact of systemic anti-inflammatory therapy on the skin fungal microbiome is poorly understood. To examine the effects of cytokine inhibition on the fungal community on human skin and oral mucosa, we analyzed the composition of the skin mycobiome before and after IL-23 inhibition. Methods: The study enrolled 15 psoriasis patients. Swab samples were collected from the psoriasis-free skin of antecubital fossa, post-auricular, and the tongue surface before and after 16 weeks of treatment with anti-IL-23 antibodies. Fungal DNA was sequenced by ITS1 metagenomic analysis, and taxonomic classification was performed. Results: Data from samples collected from the antecubital fossa revealed that the α diversity of the skin mycobiome decreased significantly after treatment with anti-IL-23 antibodies (p = 0.0120). Fungal DNAs were not amplified in 6/15 swab samples after 16 weeks of IL-23 inhibition; by contrast, sufficiently detected in all 15 samples before treatment (p = 0.0554). A comparison of 9/15 paired samples containing well-detected reads revealed that the percentage of genus Malassezia in the mycobiome fell significantly after treatment with IL-23 inhibitors (before, 29.3% ± 9.9%; after; 8.5% ± 3.4%, p = 0.0137). The mycobiome on post-auricular skin and on the tongue surface showed no marked changes after IL-23 inhibition. Conclusions: Taken together, the data suggest that inhibition of systemic IL-23 provokes dysbiosis of the mycobiome at the antecubital fossa skin, a finding characterized by reduced fungal diversity and a reduction in the percentage of the genus Malassezia.